Potential contribution of economic integration to economic growth and development in OECS countries - Rainford, Roderick G. (OECS CastriesLC, 1987)
Identifies infrastructure that should be in place so that OECS states can benefit from economic integration. Specific measures suggested include the effective removal of trade barriers; continued protection of and unimpeded access to OECS markets; the continuation of special regimes eg. the new marketing arrangements for primary agricultural products and livestock. Discusses briefly progress made in specific areas viz. The CARICOM industrial programming scheme and the CARICOM enterprise regime.